ANALISIS USAHATANI NENAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR ANALYSIS OF PINEAPPLE FARMING IN KUALU NENAS VILLAGE SUB-DISTRICT OF TAMBANG KAMPAR REGENCY - Khairani Khairani; Roza Yulida; Jumantri Yusri (Universitas Lancang Kuning, 2015)
ABSTRACT The purpose of this research are: 1) analyze of the pineapple farm income in Kualu Nenas Village; 2) analyze of the efficiency farming in Kualu Nenas Village. This research was conducted in Kualu Nenas Village Tambang District Kampar Regency by using survey method. The technique was taken respondents by simple random sampling. The populations of this research are pineapple farmers with the 67 peoples were chosen at random to 35 farmers. Analysis of the data used is the analysis of farming .The results showed that the total cost of production of pineapple farm on one year in the village Kualu Nenas is Rp.29.988.505,94-/ha, with the average of pineapple production is 34.592 pieces/ha/year in order to be obtain net income with the average is Rp.47,047,110.50/year. Pineapple farm in the Kualu Nenas Village are efficient by showned of Return Cost Ratio (RCR) >1 (2.57). It means, for Rp.1,- come out will be increasing income obtained Rp.2,57, thus indicated that pineapple farming in the Kualu Nenas Village economically efficient and feasible to be continued and developed.